Midrash, Apocrypha, Culture Medium and Development Of Doctrine: Some Facts in Quest Of A Terminology - McNamara, Martin (Apocrypha, 1995)
Midrash has been traditionally regarded as something specifically Jewish and rabbinic, but later as a reality found already in the Hebrew Scriptures and present also in New Testament writings. In this essay the more recent debates regarding the nature of midrash are examined in the larger context of inner-biblical exegesis and against the background of canonical process. Some midrash-type features or techniques are examined and these are seen to be found also in apocryhal and traditional Christian commentary literature. In the light of this there is a consideration of the reflection on the afterlife in Irish apocrypha and Irish theological treatises.